Plasma proteomic biomarkers predict therapeutic responses in advanced biliary tract cancer patients receiving Camrelizumab plus the GEMOX treatment - Shiyun Cui; Hejian Zheng; Yiyang Xu; Qiuyu Wu; Weici Liu; Yucheng Cai; Lei Fan; Yitong Tian; Hao Qian; Yuting Ding; Xinyi Zhang; Jiaguang Zhang; et al. (npj Precision Oncology)
Abstract Biliary tract cancer (BTC) has greatly influenced patient survival for years. Nowadays, immunotherapy represents a promising breakthrough and proteomics is one of powerful technologies in biomarker research. We collected plasma and tissue samples from 37 patients with advanced BTC and 92 proteins were analyzed by proximity extension assay (PEA). Through linear mixed effect models, compared to partial response (PR) group, 8 proteins, IL7, ANGPT2, IL15, HO-1, CXCL1, CXCL5, IL33, and VEGFA, exhibited significantly higher expression in stable disease and progressive disease (SD_PD) group in response-effect analysis. It was also revealed that a subset of proteins increased over time, including PDCD1, TNFRSF4, DCN, CRTAM, VEGFR-2 and ADA in PR group and PDCD1, IL10, ADA, CD28, and PTN in SD_PD group. In interaction-effect analysis, HO-1, ANGPT2, IL15 were three significant differentially expressed proteins (DEPs). Receiver operating characteristic (ROC) analysis further demonstrated that HO-1, ANGPT2, IL15 showed high accuracy in patients with immune checkpoint blockade (ICB) treatment plus chemotherapy (AUC = 0.74). In addition, based on the obtained plasma and tissue samples, two nomogram models were constructed for predicting the prognosis of BTC by genome combined with proteomics. Collectively meaningful proteomic biomarkers are beneficial to evaluate the efficacy of immunotherapy, and these discovered biomarkers may be included in the scope of treatments’ evaluation and improvement in future study.